Towards a healthy stomach? Helicobacter pylori prevalence has dramatically decreased over 23 years in adults in a Swedish community. Issue 5 (1st October 2016) - Agréus, Lars; Hellström, Per M; Talley, Nicholas J; Wallner, Bengt; Forsberg, Anna; Vieth, Michael; Veits, Lothar; Björkegren, Karin; Engstrand, Lars; Andreasson, Anna
Abstract : Background: In Western countries the prevalence of Helicobacter pylori (H. pylori) infection may be declining but there is a lack of recent longitudinal population studies. We evaluated the changing epidemiology over a 23‐year period in Sweden. Materials and methods: In 1989, the validated Abdominal Symptom Questionnaire (ASQ) was mailed to a random sample of inhabitants (ages 22–80 years) in a Swedish community, and 1097 (87%) responded. H. pylori serology was analysed in a representative subsample ( n  = 145). Twenty‐three years later, the ASQ was mailed again using similar selection criteria, and 388 out of 1036 responders had an upper endoscopy with assessment of H. pylori and corpus atrophy status. Results: The prevalence of positive H. pylori serology decreased from 37.9% (1989) to 15.8% (2012), corresponding to a decrease in odds of 75% per decade (odds ratio (OR): 0.25; 95% confidence interval (CI): 0.11–0.59, p  = 0.001) independent of age, gender, body mass index (BMI) and level of education, with a pattern consistent with a birth cohort effect. The prevalence increased with increasing age ( p  = 0.001). The prevalence of H. pylori on histology in 2012 was 11.4% (95% CI 8.6–15.0). The prevalence of corpus atrophy on serology and/or histology in 2012 was 3.2% (95% CI 1.8–5.5); all cases were ≥57 years old. Conclusion: The stomach is healthier in 2012 compared with 1989. H. pylori prevalence in adults has decreased over the last two decades to a level where clinical management might be affected.